2020 Updates on tocilizumab indications for clinicians managing patients with severe acute respiratory syndrome coronavirus 2 - Mohammed A Omair; Waleed Hafiz; Mohammad Mustafa; Leen Ghoniam; Abdulrahman Alreshaid; Ibrahim Almaghlouth; Mazin Barry (Wolters Kluwer Medknow Publications, 2020)
In March 2020, the World Health Organization declared coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2, as a global pandemic. The number of infected individuals has grown exponentially, and no vaccine candidate is currently available. Hence, various drugs are being considered for the treatment of patients with COVID-19. Tocilizumab, a novel humanized monoclonal antibody targeting interleukin-6 (IL-6) receptor, has been approved for the treatment of various inflammatory conditions, including moderate-to-severe rheumatoid arthritis, giant cell arteritis, active polyarticular and systemic juvenile idiopathic arthritis in patients aged ≥2 years, and Castleman disease. Given that patients with severe COVID-19 show features of an accentuated immune response and increased release of many proinflammatory cytokines, including IL-6, tocilizumab has been repurposed as a possible COVID-19 therapy. This review provides clinicians managing patients with COVID-19 with an overview of the IL-6 pathway, its blockade by tocilizumab, and the effects of this drug in various inflammatory conditions, including current understanding of its effects in patients with COVID-19. Tocilizumab is listed as an option for treating severe or critical cases of COVID-19 with elevated IL-6 in the 7th edition of the National Health Commission of the People's Republic of China COVID-19 Diagnosis and Treatment Guide. A systematic review of six small observational studies and case reports on the supportive use of tocilizumab in patients with COVID-19 suggested some benefits of the treatment but did not allow solid conclusions; further clinical trials are currently evaluating the impact of adding tocilizumab to the treatment regimen for these patients.